The worst television is better than no television - Muanis, Felipe De Castro (Matrizes, 2015)
The discussion of a program quality by means of a communication process with its viewer makes generalizations impossible. The constant criticism to television refers, primarily, to its contents, but it is also form, broadcasting, medium and a communi-cation process through which the audience can interrelate in a hermeneutical style, taking Gadamer’s theory — which advocates that one interprets something from one’s own history and experience. If what is said on television is more important than what is shown, then its quality is less in its content and more in its capacity to create communication and generate discussion between its viewers and society, although the latter frequently addresses programs as being low quality.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2MDYvaXNzbi4xOTgyLTgxNjAudjlpMXA4Ny0xMDE